Research of energy efficiency and reduction of environmental pollution in freight rail transportation - Lebedevas, Sergejus; Dailydka, Stasys; Jastremskas, Virgilijus; Rapalis, Paulius (Transport, 2017)
The publication presents the results arising from the experimental and mathematical modelling studies, which mainly aimed to investigate the selection and optimization of the rational operation modes particular to diesel engines of freight locomotives in the possession of the JSC ‘Lithuanian Railways’ (AB ‘Lietuvos geležinkeliai’). The goal of the optimization is to increase the energy efficiency, reduce fuel consumption and emissions of harmful air pollutants to the environment from diesel engines of locomotives during freight transportation via the main lines of the Lithuanian railway network. A complex energy efficiency and environmental pollution assessment criterion KE–E adjusted for diesel engines of freight locomotives has been suggested. The use of KE–E on the basis of the conducted complex experimental mathematical computer modelling studies has determined that the reserves reducing fuel consumption, harmful emissions and greenhouse gas (CO2) emissions constitute 6÷15% on an average, and in the case of individual railway network lines they go up to 30%. The comparative emission of harmful components per fuel mass (NOx, CO, CH, PM) e´NOx, e´CO, e´CH, e´PM when carrying freight via the main lines of the railway network by trains weighing 3000÷7500 t has been singled out. The results constitute sufficient grounds to organise control of harmful emissions and provide an opportunity to solve practical tasks with a slight tolerance (3÷7%) taking account of diesel engines of locomotives used for transportation. It has been proposed to measure the freight transportation efficiency according to the complex criterion KE–E, indicates the energy efficiency and the assessment of environmental pollution originating from diesel engine of locomotives. The reserves for increasing the efficiency of energy usage have been studied according to the variational mathematical computer modelling data. A methodology for measuring the freight transportation rationality and estimating the optimal indicators has been proposed, using the values of the KE–E criterion for the railways freight transportation, as well as the technology for controlling the traction characteristics as well as energy and ecology indicators of diesel engines of locomotives in operational conditions. First published online: 20 Oct 2016